2013
DOI: 10.1017/s1751731113000268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l-carnitine supplementation to suckling piglets on carcass and meat quality at market age

Abstract: In a previous study, carnitine supplementation to piglets during the suckling period resulted in an increased total muscle fibre number at weaning in piglets of low birth weight. The objective of the present study was to investigate whether this effect is maintained until market age and whether this would attenuate the negative consequences of low birth weight on carcass and meat quality. Using a split-plot design with litter as block, sex as whole plot and treatment as subplot, the effects of earlypostnatal L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Furthermore, investigating the impact of gestational supplementation on hyperplasia especially in post-weaning pigs would be of great importance, as results on this matter are contradictory. For instance, supplementing l -carnitine daily to L-BtW piglets during the suckling period resulted in a third wave of hyperplasia [41] during the nursing period, but no difference in TNF was found between control and l -carnitine supplemented pigs at the age of slaughter [42]. Based on this contradiction, one could speculate that changes occurring during the prenatal period are more manifested and less prone to environmental changes in the postnatal period, thus, having permanent positive effects until the animal reaches slaughter weight.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, investigating the impact of gestational supplementation on hyperplasia especially in post-weaning pigs would be of great importance, as results on this matter are contradictory. For instance, supplementing l -carnitine daily to L-BtW piglets during the suckling period resulted in a third wave of hyperplasia [41] during the nursing period, but no difference in TNF was found between control and l -carnitine supplemented pigs at the age of slaughter [42]. Based on this contradiction, one could speculate that changes occurring during the prenatal period are more manifested and less prone to environmental changes in the postnatal period, thus, having permanent positive effects until the animal reaches slaughter weight.…”
Section: Resultsmentioning
confidence: 99%
“…The piglets were exclusively suckling (no creep‐feed was offered), and thus, no additional L‐carnitine was taken up than from sow's milk. In a subsequent study from Lösel and Rehfeldt (), in which low‐birth weight piglets ( n = 56 female and castrated male from 14 German Landrace sows) were orally supplemented with 400 mg L‐carnitine per day during the suckling period (from day 7 to 27 of age) and fed standard diets from weaning at day 28 of age until slaughter at day 166 of age, it was shown that growth performance, body composition, measures of meat yield and fat accretion and muscle contractile traits at slaughter were not influenced by supplemental L‐carnitine. In contrast to the before‐mentioned study of this group, piglets were offered creep‐feed from day 10 of age, but neither the composition nor the intake of creep‐feed by the piglets have been reported in this study.…”
Section: Efficacy Of L‐carnitine Supplementation On Performance Of Momentioning
confidence: 99%
“…In general, carnitine concentrations in tissues of pigs are markedly lower than those reported for humans [15]. For example, free carnitine levels in pig plasma at day 28 are shown to be 18.4 µmol/L and increased up to 37.7 µmol/L after 20 days LC dietary supplementation at 400 mg/ day [38]. Plasma carnitine concentration is comparable with those of other antioxidants, including vitamin E (20-30 µM) and ascorbic acid (26.1-84.6 µM) [39].…”
Section: Absorption and Metabolism Of Carnitinementioning
confidence: 79%